PERSPEKTIF CIRI DAN TUGAS PERKEMBANGAN REMAJA DALAM KAJIAN PENDIDIKAN AGAMA KRISTEN - Dorlan Naibaho; Feni Sulistiani Sitorus; Yohana Olivia Sitorus (CV. Denasya Smart Publisher, 2024)
This Christian perspective helps teachers develop Christian teenagers with Christian values ​​appropriate to their age and stage of development. The aim of this research is to understand how Christian teenagers can be developed and assisted in the process of spiritual and moral development. This research method is a literature study by reviewing literature, collecting books, literature materials and references related to the research being carried out. Data collection techniques include observations, interviews and documentation. The research results show that the perspective of characteristics and tasks of adolescent development in the study of Christian Religious Education has a positive impact on students' understanding and in the development of adolescents' spirituality. It is important to understand the characteristics of their development, such as self-identity, interpersonal relationships, and exploration of spiritual values. Developmental tasks related to religious experience, such as understanding doctrine, moral formation, and applying religious principles in daily life, are also the main focus in the process of Christian religious education for adolescents. The practical implications of these findings highlight the need for an approach to religious edShalom.ucation that is holistic and relevant to the developmental needs of Christian adolescents.